SARS-CoV-2: The Monster Causes COVID-19 - Song, Chang; Li, Zesong; Li, Chen; Huang, Meiying; Liu, Jianhong; Fang, Qiuping; Cao, Zitong; Zhang, Lin; Gao, Pengbo; Nie, Wendi; Luo, Xueyao; Kang, Jianhao; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Coronaviruses are viruses whose particles look like crowns. SARS-CoV-2 is the seventh member of the human coronavirus family to cause COVID-19 which is regarded as a once-in-a-century pandemic worldwide. It holds has the characteristics of a pandemic, which has broy -55ught many serious negative impacts to human beings. It may take time for humans to fight the pandemic. In addition to humans, SARS-CoV-2 also infects animals such as cats. This review introduces the origins, structures, pathogenic mechanisms, characteristics of transmission, detection and diagnosis, evolution and variation of SARS-CoV-2. We summarized the clinical characteristics, the strategies for treatment and prevention of COVID-19, and analyzed the problems and challenges we face.